Prediction of distal residue participation in enzyme catalysis. (2nd April 2015) - Brodkin, Heather R.; DeLateur, Nicholas A.; Somarowthu, Srinivas; Mills, Caitlyn L.; Novak, Walter R.; Beuning, Penny J.; Ringe, Dagmar; Ondrechen, Mary Jo
Abstract: A scoring method for the prediction of catalytically important residues in enzyme structures is presented and used to examine the participation of distal residues in enzyme catalysis. Scores are based on the Partial Order Optimum Likelihood (POOL) machine learning method, using computed electrostatic properties, surface geometric features, and information obtained from the phylogenetic tree as input features. Predictions of distal residue participation in catalysis are compared with experimental kinetics data from the literature on variants of the featured enzymes; some additional kinetics measurements are reported for variants of Pseudomonas putida nitrile hydratase (ppNH) and for E scherichia coli alkaline phosphatase (AP). The multilayer active sites of P . putida nitrile hydratase and of human phosphoglucose isomerase are predicted by the POOL log ZP scores, as is the single‐layer active site of P . putida ketosteroid isomerase. Thelog ZP score cutoff utilized here results in over‐prediction of distal residue involvement in E. coli alkaline phosphatase. While fewer experimental data points are available for P . putida mandelate racemase and for human carbonic anhydrase II, the POOLlog ZP scores properly predict the previously reported participation of distal residues.